The role of cystinosin in the intermediary thjiol metabolism and redox homeostasis in kidney proximal tubular cells - Sumayao, Rodolfo E., Jr. (Animo Repository, 2018)
Cystinosin is a lysosomal transmembrane protein which facilitates transport of the disulphide amino acid cystine (CySS) from the lysosomes of the cell. This protein is encoded by the CTNS gene which is defective in the lysosomal storage disorder, cystinosis. Because of the apparent involvement of cystinosin in the intermediary thiol metabolism, its discovery has fuelled investigations into its role in modulating cellular redox homeostasis. The kidney proximal tubular cells (PTCs) have become the focus of various studies on cystinosin since the protein is highly expressed in these cells and kidney proximal tubular transport dysfunction is the foremost clinical manifestation of cystinosis. The lysosomal CySS pool is a major source of cytosolic cysteine (Cys), the limiting amino acid for the synthesis of an important antioxidant glutathione (GSH) via the γ-glutamyl cycle. Therefore, loss of cystinosin function is presumed to lead to cytosolic deficit of Cys which may impair GSH synthesis. However, studies using in vitro models lacking cystinosin yielded inconsistent results and failed to establish the mechanistic role of cystinosin in modulating GSH synthesis and redox homeostasis. Because of the complexity of the metabolic micro- and macro-environment in vivo, using in vitro models alone may not be able to capture the complete sequence of biochemical and physiological events that occur as a consequence of loss of cystinosin function. The coexistence of pathways for the overall handling and disposition of GSH, the modulation of CTNS gene by intracellular redox status and the existence of a non-canonical isoform of cystinosin may constitute possible rescue mechanisms in vivo to remediate redox perturbations in renal PTCs. Importantly, the mitochondria seem to play a critical role in orchestrating redox imbalances initiated by cystinosin dysfunction. Non-invasive techniques such as in vivo magnetic resonance imaging with the aid of systems biology approaches may provide invaluable mechanistic insights into the role of cystinosin in the essential intermediary thiol metabolism and in the overall regulation cellular redox homeostasis.